Senior cycle review: Analysis of discussions in schools on senior cycle pathways and structures in Ireland - Emer Smyth (The Economic and Social Research Institute (ESRI), 2019)
This report is intended to inform the National Council for Curriculum and Assessment (NCCA) review of senior cycle and draws on the second cycle of the consultation process with 41 schools with different profiles and characteristics. Building on the first cycle which examined the purpose of senior cycle, the second cycle focused more specifically on pathways and structures within the senior cycle and on the kinds of learning experiences teachers, students and parents would like to see. The findings point to a consensus across all groups on the need to spread assessment over the course of senior cycle and adopt a greater variety of assessment approaches.
Keywords: 330; upper secondary education; curriculum